2017
DOI: 10.20884/1.sb.2017.4.2.378
|View full text |Cite
|
Sign up to set email alerts
|

RESISTENSI <em>Klebsiella</em> sp TERHADAP MEROPENEM DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO

Abstract: Resistant Gram-negative bacteria, particularly Klebsiella sp., has become a serious problem in hospitals as one of the main causes of nosocomial infections spread through urine catheterization. Infections of Klebsiella sp. producing extended-spectrum beta-lactamase (ESBL) can lead to significant economic and clinical negative outcome. This study was aimed to determine the sensitivity of ESBL Klebsiella sp. against meropenem as a cause of nosocomial infections in Prof. Dr. Margono Soekarjo hospital. This resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A previous study conducted at the Government Hospital in the Banyumas Regency, Central Java Indonesia, reported that 2 out of 40 Klebsiella pneumoniae analyzed were resistant to antibiotics (Afifah et al, 2017). These bacteria contribute to healthcare-associated illnesses and are the most frequent cause of urinary tract infections in hospital (Musdalipah, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study conducted at the Government Hospital in the Banyumas Regency, Central Java Indonesia, reported that 2 out of 40 Klebsiella pneumoniae analyzed were resistant to antibiotics (Afifah et al, 2017). These bacteria contribute to healthcare-associated illnesses and are the most frequent cause of urinary tract infections in hospital (Musdalipah, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance, often referred to as the alarming bacteria, is a life-threatening problem in many regions of the world (Afifah et al, 2017). Antibiotic resistance is predicted to kill 10 million population worldwide by 2050, with 4.7 million dying in Asia if the problem is not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, in Margono Soekarjo General Hospital, the resistance of Klebsiella to meropenem was reported. 13 Antibiotic resistance is a primary cause of antibiotic therapy failure in patients with sepsis and septic shock, raising the mortality rate in hospitals. Biofilm formation by sepsis-causing bacteria is another factor that contributes to the ineffectiveness of sepsis patients' treatment.…”
Section: Introductionmentioning
confidence: 99%